Body posture in the sagittal plane and the path length among girls and boys at school age - Jacek Wilczyński (Studia Medyczne, 2014)
Introduction : The most frequently studied and most valuable postural reactions include the path length. Aim of the research study: The analysis of the relation between the quality of postures in the sagittal plane and the path length ofposturograms in girls and boys at school age. Material and methods: The research included 503 girls and boys aged 12–15 years. The research approach used a spatial photogrammetry technique using the effect of projection moiré. The path length was tested on an R50300 Cosmogamma platform by Emildue. Results : There were significant differences in the path length between girls and boys; the path was significantly shorter in girls, both in the test with eyes open and eyes closed. A post hoc analysis (Bonferroni test) confirmed the significance. A significant effect of study options was also shown. With eyes closed there was lengthening of the path in 12-year-old girls and 12- and 15-year-old boys, whereas in the other groups it was shortened. In addition, there was demonstrated a significant interaction of gender and age, a significant interaction of gender and study options and a significant interaction of age and study options. There were no significant differences in path length in relation to age. Analysis of variance with the double classification showed no significant relation between the path length and the quality of the posture in the sagittal plane. Conclusions: The issue of relations between body posture in the sagittal plane and the path length of the centre of feet pressure requires further research and analysis.